2017
DOI: 10.1002/jbmr.3227
|View full text |Cite|
|
Sign up to set email alerts
|

An Ectosteric Inhibitor of Cathepsin K Inhibits Bone Resorption in Ovariectomized Mice

Abstract: The potent cathepsin K (CatK) inhibitor, Tanshinone IIA sulfonic sodium (T06), was tested for its in vitro and in vivo antiresorptive activities. T06 binds in an ectosteric site of CatK remote from its active site and selectively inhibits collagen degradation with an IC value of 2.7 ± 0.2 μM (CatK:T06 molar ratio of 1:5). However, it does not suppress fluorogenic peptide cleavage and gelatinolysis at a 2500-fold molar excess. Contrary to active site-directed CatK inhibitors, such as odanacatib, T06 suppresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Our earlier study showed that 90% of the trenches start as a pit [ 15 ] and that sufficient cathepsin K activity is an absolute prerequisite to switch from pit to trench mode. The main evidence supporting this finding is that increasing concentrations of odanacatib in bone resorption assays lead to decreasing trench surface (down to an almost complete abolishment at higher concentrations) and concomitantly increasing pit surface [ 18 , 33 ]. This concomitant effect on trench and pit formation is confirmed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier study showed that 90% of the trenches start as a pit [ 15 ] and that sufficient cathepsin K activity is an absolute prerequisite to switch from pit to trench mode. The main evidence supporting this finding is that increasing concentrations of odanacatib in bone resorption assays lead to decreasing trench surface (down to an almost complete abolishment at higher concentrations) and concomitantly increasing pit surface [ 18 , 33 ]. This concomitant effect on trench and pit formation is confirmed here.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the key contribution of cathepsin K to bone resorption is collagen degradation [ 3 ]. Accordingly, cathepsin K-rich OCs making trenches leave very little undegraded demineralized collagenous matrix at the bottom of the trenches, whereas cathepsin K-poor OCs making pits leave variable, but significant amounts of undegraded demineralized collagenous matrix at the bottom of the pit [ 17 , 33 , 34 ]. Because collagen is a negative regulator of OC bone resorptive activity [ 35 , 36 , 37 ], these observations led to a model where accumulation of demineralized collagen makes the OC stop resorbing and migrating right away, so that cathepsin K-poor OCs perform intermittent resorption (alternations of resorption and migration) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 value for compound 1 in the osteoclast resorption assay was 312 nM. This is close to the IC 50 value of tanshinone IIA sulfonate (240 nM), which showed efficacy in ovariectomiced mice [ 18 ]. The overall potency is still about 15–20 times lower than for the most potent active site-directed CatK inhibitor, odanacatib [ 17 ] but may have the advantage of avoiding side effects seen with odanacatib and other CatK inhibitors [ 13 , 45 ].…”
Section: Discussionmentioning
confidence: 54%
“…Ectosteric inhibitors targeting these sites will thus represent substrate specific inhibitors, which selectively can block the disease-relevant activities of cathepsins. We have recently demonstrated that the selective inhibition of the enzyme’s collagenase activity in osteoclast bone-resorption assays and in an osteoporosis mouse model can be achieved without blocking its TGF-ß1 degrading activity correlated to some of the side effects seen in CatK inhibitor clinical trials [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone IIA sulfonic sodium, salvianolic acid B, glycyrrhizin, brucine, strychnine, cryptotanshinone, and liquiritin are major compounds present in Bi-Qi extract [ 6 , 7 ]. Tanshinone IIA sulfonic sodium is a water-soluble extract from Radix et Rhizoma S. miltiorrhizae with a strong anti-osteoporotic property [ 8 ]. Bi-Qi has been shown to have anti-inflammatory and analgesic properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%